2022
DOI: 10.1002/adsc.202101469
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Reaction of Anthranils with Alkynyl Sulfones for the Regioselective Formation of 3‐Hydroxyquinolines

Abstract: The gold-catalyzed regioselective formation of 3-hydroxyquinoline is accessed by combining anthranils and alkynyl sulfones. The selective scission of the epoxide intermediate stems from the thermodynamic stability difference of the resultant cation according to quantum chemical calculations. The subsequent semi-pinacol rearrangement leads to the 1,2-shift of an aryl or alkyl group originating from the sulfone. A gram-scale synthesis of 3hydroxyquinoline further manifests the viability of the protocol for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Transformations that lead to rearrangements with a tethered nucleophilic functional group can rapidly generate multiple cyclic frameworks with high sp 3 ‐content and an increasing number of stereocenters in a single operation. Such features render homogenous gold catalysis attractive for optimizing molecular complexity [10–21] . We expect that gold carbene chemistry in conjunction with rearrangement/migration offers an efficient approach to propellane‐type scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Transformations that lead to rearrangements with a tethered nucleophilic functional group can rapidly generate multiple cyclic frameworks with high sp 3 ‐content and an increasing number of stereocenters in a single operation. Such features render homogenous gold catalysis attractive for optimizing molecular complexity [10–21] . We expect that gold carbene chemistry in conjunction with rearrangement/migration offers an efficient approach to propellane‐type scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…[17,20] The relevant transformations of electron-deficient alkynes, which exhibit a significant inertness toward oxidation, are poorly studied; the reported examples include only alkynylcarbonyls such as propiolates or ynones. [21][22][23][24][25] Alkynylsulfones -electron-deficient alkynes bearing accepting sulfone fragments -were recognized as versatile reagents for alkynylations, [26][27][28][29] and, in addition, these species are also often used as building blocks in cycloadditions, [30][31][32][33] nucleophilic additions, [34,35] or coupling reactions. [36,37] We have recently shown that alkynylsulfones can be readily hydrated under gold-catalyzed conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Alkynylsulfones – electron‐deficient alkynes bearing accepting sulfone fragments – were recognized as versatile reagents for alkynylations, [26–29] and, in addition, these species are also often used as building blocks in cycloadditions, [30–33] nucleophilic additions, [34,35] or coupling reactions [36,37] . We have recently shown that alkynylsulfones can be readily hydrated under gold‐catalyzed conditions [38] .…”
Section: Introductionmentioning
confidence: 99%
“…1 Among the methods established for preparing cyclopropanes, 2 gold-catalyzed reactions of nitrene transfer have been known as a promising methodology for the synthesis of bioactive miscellaneous aza-heterocyclic compounds. 3 Considerable effort has been devoted to developing transfer reagents, such as triazapentalene, 4 2 H -azirines, 5 azides, 6 isoxazole derivatives, 7 anthranils, 8 azirines, 9 pyridine-based aza-ylides 10 and sulfilimines, 11 to trap α-imino gold carbenes as key electrophilic intermediates en route to functional materials and aza-heterocycles (Scheme 1). Among these synthetic strategies for the generation of α-imino gold carbenes, unsatisfactorily, many nitrene transfer reagents exhibit substantial drawbacks, such as azides with potential explosivity and ylides with poor reactivity.…”
Section: Introductionmentioning
confidence: 99%